2011
DOI: 10.1183/09031936.00170110
|View full text |Cite
|
Sign up to set email alerts
|

Different inflammatory phenotypes in adults and children with acute asthma

Abstract: Inflammatory phenotypes are recognised in stable adult asthma, but are less well established in childhood and acute asthma. Additionally, Chlamydophila pneumoniae infection as a cause of noneosinophilic asthma is controversial. This study examined the prevalence of inflammatory phenotypes and the presence of current C. pneumoniae infection in adults and children with stable and acute asthma.Adults with stable (n529) or acute (n522) asthma, healthy adults (n511), children with stable (n549) or acute (n528) asth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
134
1
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(147 citation statements)
references
References 29 publications
4
134
1
4
Order By: Relevance
“…Many studies have shown an association between the severity of asthma and neutrophilic inflammation detected by induced sputum [24,25]. Furthermore, our study supports the findings of SIROUX et al [26] who reported that the phenotype of ''active treated allergic childhood-onset asthma'' is associated with blood eosinophilia, while ''active treated adult-onset asthma'' is associated with blood neutrophils.…”
Section: Asthma With Severe Exacerbations and Multiple Allergiessupporting
confidence: 91%
“…Many studies have shown an association between the severity of asthma and neutrophilic inflammation detected by induced sputum [24,25]. Furthermore, our study supports the findings of SIROUX et al [26] who reported that the phenotype of ''active treated allergic childhood-onset asthma'' is associated with blood eosinophilia, while ''active treated adult-onset asthma'' is associated with blood neutrophils.…”
Section: Asthma With Severe Exacerbations and Multiple Allergiessupporting
confidence: 91%
“…Similarly, in adults on inhaled steroid therapy, the sputum inflammatory profile commonly changed in subjects with both moderate and severe asthma over 1 year, and only one-third of subjects had a stable phenotype [23]. Given the relative instability of airway inflammation in asthma and the added complication of changes in inflammation during exacerbations [24], it is unlikely that management based on inflammatory phenotype alone is sufficient. An interesting point about the subset of patients that do have persistently noneosinophilic disease is their poor response to inhaled steroids [25].…”
Section: Limitations Of Therapy Targeted At Inflammationmentioning
confidence: 99%
“…However, as longitudinal studies are lacking, it remains unclear whether neutrophilic asthma developed on a background of long-standing eosinophilic asthma or recurrent or persistent bacterial infections superimposed on the background of a previously eosinophilic asthma. Less is known about the incidence of neutrophilic asthma in children, where eosinophilic asthma seems to predominate both in acute and in stable disease (12). Neutrophilic inflammation appears more frequent in children with nonatopic asthma (36).…”
Section: Noneosinophilic Asthmamentioning
confidence: 99%
“…In addition, inflammatory phenotypes appear to differ with age. Eosinophilic inflammation is more prevalent in both acute and stable childhood asthma, while neutrophilic inflammation is more frequent in acute asthma in older adults (12). In intrinsic asthma, which is frequently of late onset, eosinophils predominate (13).…”
mentioning
confidence: 99%